2022
DOI: 10.1186/s12884-022-04552-y
|View full text |Cite|
|
Sign up to set email alerts
|

The role of maternal age on the risk of preterm birth among singletons and multiples: a retrospective cohort study in Lombardy, Northern Italy

Abstract: Background All over the world, especially in the developed countries, maternal age at birth is rising. This study aimed to assess the role of maternal age on the occurrence of preterm birth (PTB) in a large birth cohort of Lombardy Region, Northern Italy. Methods This population-based study used data from regional healthcare utilization databases of Lombardy to identify women who delivered between 2007 and 2017. PTBs were defined as births before 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The relationship between residential area and preterm birth is assumed to be due to environmental factors, including socio-economic conditions and environmental conditions, such as pollution levels and water quality. Access to health services and the presence of health workers who can help mothers must also be considered [ 25 27 ]. A study conducted by Malwela et al [ 28 ], in rural areas in South Africa, shows that the cause of the increasing incidence of preterm births is the availability of equipment, which is less than 40%, making preterm births unpreventable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between residential area and preterm birth is assumed to be due to environmental factors, including socio-economic conditions and environmental conditions, such as pollution levels and water quality. Access to health services and the presence of health workers who can help mothers must also be considered [ 25 27 ]. A study conducted by Malwela et al [ 28 ], in rural areas in South Africa, shows that the cause of the increasing incidence of preterm births is the availability of equipment, which is less than 40%, making preterm births unpreventable.…”
Section: Discussionmentioning
confidence: 99%
“…The fetus’s only supply of this fatty acid comes from the mother’s body’s storage of EPA and DHA. The growing intrauterine fetus actively receives both EPA and DHA through the placenta [ 25 28 ]. Therefore, women with adequate omega-3 intake early in pregnancy should maintain such intake.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, in recent decades, with the increase in the PB rate, there is an increase in maternal age, but this relationship remains controversial. While some studies have found that maternal age is independently associated with PB [ 23 , 24 ], other studies have noted that both advanced maternal age and younger age have the same risk of PB [ 25 ]. The results of our study showed a mean age of 34.73 years (±5.32 years) in patients with PB, compared to 29.73 years (±8.48 years) in patients with TB, noting that there was a statistically significant difference between the two categories of TB/PB in terms of patient age.…”
Section: Discussionmentioning
confidence: 99%
“…The main outcome of this study was the occurrence of preterm birth. Preterm birth was defined as <37 weeks gestation ( 1 ). IVF is considered an assisted reproductive technology (ART).…”
Section: Methodsmentioning
confidence: 99%
“…Preterm birth is defined as delivery at less than 37 completed weeks or 259 days of gestation; it has become one of the most important obstetric issues and is the main cause of perinatal morbidity and mortality ( 1 ). In addition, preterm birth is associated with increased health care costs ( 2 ).…”
Section: Introductionmentioning
confidence: 99%